Project 253-3: Wintering, grazing and fattening heifers. - Smith, E.F.; Cox, R.F.; Good, D.L.; Mackintosh, D.L. (Kansas Agricultural Experiment Station, 2012)
Seventy good quality Hereford heifer calves were purchased for $31.50 a hundredweight in east central Kansas and received October 1, 1951. The pay weight was 425 pounds per head. It was necessary to dehorn most of the heifers after they were received. They were started on test November 30, 1951, at an average weight of about 440 pounds. Five heifers were removed from different lots during the wintering period, two because of lead paint poisoning and three because of no gain.
Keywords: Beef; Heifers; Grazing; Grain; Gain